2012
DOI: 10.1590/s0100-40422012000700019
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento e caracterização de nanopartículas lipídicas destinadas à aplicação tópica de dapsona

Abstract: Recebido em 26/10/11; aceito em 3/3/12; publicado na web em 15/6/12 DEVELOPMENT AND CHARACTERIZATION OF LIPID NANOPARTICLES FOR DAPSONE TOPICAL APPLICATION. In this work, theospheres (innovative lipid nanoparticles) were prepared by the high pressure homogenization technique using different surfactants for dapsone encapsulation. Mean particle size ranged from 105 to 153 nm and negative zeta potentials were obtained for all theosphere formulations. Atomic force microscopy images confirmed the spherical shape of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
(45 reference statements)
0
0
0
1
Order By: Relevance
“…Alternativamente, contaminação microbiológicas também podem resultar em variação do pH e possível acidificação do meio. Um possível uso de conservante é o imidazolinidil uréia 0,5% [15] que já foi previamente utilizado em nanopartículas sólidas com manteigas vegetais brasileiras.…”
Section: Caracterização Do Clnunclassified
“…Alternativamente, contaminação microbiológicas também podem resultar em variação do pH e possível acidificação do meio. Um possível uso de conservante é o imidazolinidil uréia 0,5% [15] que já foi previamente utilizado em nanopartículas sólidas com manteigas vegetais brasileiras.…”
Section: Caracterização Do Clnunclassified
“…Changes in the ZP can be observed over time, being indicators of system destabilization, with consequent expulsions of the incorporated compounds during the storage period (Bunjes, 2005;Shah, Eldridge, Palombo, Harding, 2015). Santos, Pereira, Bender, Colomé, & Guterres (2012) found that ZP values varied according to the emulsifying system used. The SLN were developed with an oil phase composed of cupuaçu butter and NLC composed of a mixture of cupuaçu butter and chestnut oil, using the emulsifiers soy lecithin and PSM 80.…”
Section: Zeta Potentialmentioning
confidence: 96%
“…ZP values of approximately | 30 | mV characterizes colloidal systems with good stability, where ZP values are considered optimal when they are roughly | 60 | mV. The system is susceptible to destabilization between 5 and 30 mV and the occurrence of limited flocculation can be observed; and for ZP values smaller than 5 mV the system presents a great tendency for particle coagulation (Santos, Pereira, Bender, Colomé, & Guterres, 2012;Shah, Eldridge, Palombo, Harding, 2015;, Madureira, Campos, Fonte, Nunes, Reis, Gomes, Sarmento, & Pintado, 2015.…”
Section: Zeta Potentialmentioning
confidence: 99%